2013
DOI: 10.1007/978-3-642-40361-3_53
|View full text |Cite
|
Sign up to set email alerts
|

The Value and Management Practices of Installed Base Information in Product-Service Systems

Abstract: Increasing competitive pressures have pushed manufacturers to increase the value of their offerings through the provision of Product-service systems. This shift results in an increased complexity of offerings and a higher degree of risk and responsibility taken by manufacturers concerning product availability, performance and product-enabled processes. The paper investigates the impact and potential benefits of installed base information management practices on the offering of Product-Service Systems. A case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…On the other hand, the examination of the customer behavior regarding the maintenance service activities and other operations may provide useful insights into developing new service businesses, in more advanced service 1 3 RFM customer analysis for product-oriented services and service… categories (Ala-Risku 2009; Ulaga and Reinartz 2011). This is in line with the idea of Saccani et al (2012), who suggested the examination of the potential value of the installed base information in managing current service businesses and support the development of new, more complex service offerings. Therefore, the paper examines the potential of RFM analyses both in managing productoriented service activities and in identifying new service business opportunities.…”
Section: Tentative Frameworksupporting
confidence: 74%
See 3 more Smart Citations
“…On the other hand, the examination of the customer behavior regarding the maintenance service activities and other operations may provide useful insights into developing new service businesses, in more advanced service 1 3 RFM customer analysis for product-oriented services and service… categories (Ala-Risku 2009; Ulaga and Reinartz 2011). This is in line with the idea of Saccani et al (2012), who suggested the examination of the potential value of the installed base information in managing current service businesses and support the development of new, more complex service offerings. Therefore, the paper examines the potential of RFM analyses both in managing productoriented service activities and in identifying new service business opportunities.…”
Section: Tentative Frameworksupporting
confidence: 74%
“…Our interventionist case studies from FleetCo and ProcessCo showed that there is indeed potential in using installed base information for OEMs' service business development (Ala-Risku 2009;Holmström et al 2010;Saccani et al 2012;Perminova-Harikoski et al 2015). In particular, the refined RFM analysis, as presented and preliminarily used in the cases of this paper, responds to the need for relatively simple, yet comprehensive tools for better understanding the value generation dynamics within service activities in OEMs (as suggested also by Laine et al 2012b).…”
Section: Overview Of the Contribution Of The Papermentioning
confidence: 95%
See 2 more Smart Citations
“…These savings are due to lower stock requirements and reduction in transportation costs. Saccani et al [17] applied a decision-analysis-tree approach to evaluate the value of IBI in an underwater system in a cruise vessel.…”
Section: A Valuementioning
confidence: 99%